Confirmatory Factor Analysis of Electronic Word of Mouth in Private College Students in Medan - B, Mesra; Lubis, Arlina Nurbaity; Rini, Endang Sulistya; Silalahi, Amlys Syahputra (AIBPM Publisher, 2020)
Electronic word of mouth (e-WOM) is a word-of-mouth promotion using internet-connected electronic devices. However, e-WOM among students has not been effective as it has not created any impacts on universities concerned. The purpose of this research is to evaluate e-WOM among students and direct the occurrence of positive e-WOM which will ultimately impact universities, especially private universities in Medan. This study used the confirmatory factor analysis (CFA) method to test how well measured variables represent constructs or the preformed factors. This research is quantitative involving 210 students of the fourth semester above. The data collected were processed with AMOS Program. The confirmatory factor analysis tests showed as many as 21 indicators remained in the model. The goodness-of-fit value of all models for each variable is received after the modification process.